2011
DOI: 10.1103/physrevlett.107.205002
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Broadening of Characteristicγ-Ray Emission Peaks fromC12(He3

Abstract: The spectral broadening of characteristic γ-ray emission peaks from the reaction (12)C((3)He,pγ)(14)N was measured in D((3)He) plasmas of the JET tokamak with ion cyclotron resonance heating tuned to the fundamental harmonic of (3)He. Intensities and detailed spectral shapes of γ-ray emission peaks were successfully reproduced using a physics model combining the kinetics of the reacting ions with a detailed description of the nuclear reaction differential cross sections for populating the L1-L8 (14)N excitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
120
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(123 citation statements)
references
References 22 publications
3
120
0
Order By: Relevance
“…This can be ascribed to the contribution from proton capture on boron. A more clear manifestation of -ray emission from fast protons was provided by the observation of the E  =5.5 MeV peak due to the d(p,) 3 He reaction (figure 3). The peak stands out of the background level in a statistically meaningful way.…”
Section: Results From the Fast Proton Scenariomentioning
confidence: 99%
See 3 more Smart Citations
“…This can be ascribed to the contribution from proton capture on boron. A more clear manifestation of -ray emission from fast protons was provided by the observation of the E  =5.5 MeV peak due to the d(p,) 3 He reaction (figure 3). The peak stands out of the background level in a statistically meaningful way.…”
Section: Results From the Fast Proton Scenariomentioning
confidence: 99%
“…The peak stands out of the background level in a statistically meaningful way. Figure 4 (a) shows the measured d(p,) 3 He emission peak. Superimposed to the data is a simulated spectral shape obtained by adding a constant background to the result of a Monte Carlo simulation using the MCNP code (providing the spectrum of energies deposited in the detection crystal) folded with the instrumental energy resolution W  and the expected kinetic broadening W K that results from the relative ion motion as predicted in reference [14] and first observed in reference [15] (see below).…”
Section: Results From the Fast Proton Scenariomentioning
confidence: 99%
See 2 more Smart Citations
“…Gamma-ray emission results from interactions between the energetic ions and impurities that are naturally found in the plasma [2][3][4]. Recently, γ-ray measurements at low counting rates and high energy resolution in present tokamak devices [5,6] have shown that added parameters of the fast ion energy distribution can be obtained by combining information on the intensity and shape of characteristic peaks of γ-ray reactions occurring in the plasma [7][8][9][10]. A review on neutron and gamma-ray measurements in tokamak plasmas for fast ion studies has been recently published in [3].…”
Section: Introductionmentioning
confidence: 99%